Strategická koncepce malé distribuční firmy - Brázda, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Cílem diplomové práce bude navrhnutí strategie a vytvoření plánu malé distribuční firmy , aby byla nadále chopna udržet si své postavení na trhu, byla konkurenceschopná a vykazovala udržitelný rozvoj.

The intention of this thesis is a strategy suggestion and a work out of a plan for small distributional company to enable it to keep its trade position, its competitiveness and that it would show sustainable development.
The Strategic Conception of Small Distribution Company
Keywords: distribuční činnost; strategie malých a středních podniků; služby; vedení změny; distributional activity; strategy for small and medium-sized enterprises; services; leading changes